Diskursus Ke-tauqÄ«fÄ«-an Rasm Usmani - Arifin, Zainal (SUHUF, 2010)
There are three opinions in religious discourses regarding the law of rasmÃ‚Â  Ã¢â‚¬ËœuÃ‚Â£mÃ„ÂnÃ„Â«Ã‚Â  in QurÃ¢â‚¬â„¢an writings. The first opinion states thatÃ‚Â  rasm Ã¢â‚¬ËœuÃ‚Â£mÃ„ÂnÃ„Â« is tauqÃ„Â«fÃ„Â« (taken for granted from Prophet Muhammad saw), the second states that it is ijtihÃ„ÂdÃ„Â«, and the last is the most moderate opinion intended to give flexibility to the average person to adapt with the QurÃ¢â‚¬â„¢an.Ã‚Â  On the other side, it also emphasizes that certain people (khawÃ„ÂÃ‚Â¡) ought to maintain the preservation ofÃ‚Â  rasmÃ‚Â  Ã¢â‚¬ËœuÃ‚Â£mÃ„ÂnÃ„Â«.Ã‚Â  The paperÃ¢â‚¬â„¢s author asks since when did the doctrine that statesÃ‚Â  rasm Ã¢â‚¬ËœuÃ‚Â£mÃ„ÂnÃ„Â«Ã‚Â  isÃ‚Â  tauqÃ„Â«fÃ„Â«Ã‚Â  exist? Has this doctrine been known since the beginning of the era of Islam?